Analysis of Zakat, Infaq, Sadaqah (ZIS), HDI, Inflation, and GRDP on Poverty Alleviation in Indonesia - Hariyanto Hariyanto; Bariyyatin Nafi'ah (ITB AAS INDONESIA Surakarta, 2023)
This study aims to analyze ZIS, inflation, HDI, and GRDP per capita on poverty alleviation in Indonesia (2015-2020 period) by using secondary data and panel data regression analysis method Random Effect Model (REM) is used to obtain an overview of the relationship between one variable and another variable. This study consists of 34 provinces in Indonesia for 6 years (2015-2020). Based on the regression results using REM, ZIS coefficient and probability value are 0.311 and 0.005, which means ZIS affect positively poverty alleviation. The coefficient and probability value of HDI are -0.252 and 0.000, meaning that HDI affects negatively poverty alleviation. the coefficient and probability value of inflation of -0.013 and 0.769 and GRDP of 0.073 and 0.668 which means have no effect on poverty alleviation in 34 provinces in Indonesia.